2017
DOI: 10.1016/j.electacta.2017.04.101
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CVD multilayered graphene as negative electrode for lithium-ion batteries

Abstract: Multilayered graphene (MLG) grown by chemical vapor deposition (CVD) was examined as a negative electrode for lithium-ion batteries. Experimental parameters such as deposition time and temperature were examined to produce carbon loadings between 0.06 -0.17 mg cm -2 and film thicknesses in the 1µm range. The MLG thin films obtained on nickel substrate were used without conductive additive and binding agent in electrochemical tests to produce a capacity of ~250 mAh.g -1 at the 5C rate. Films were further charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 42 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The nanocomposite was tested as an anode in button lithium-ion battery giving a high energy capacity, yet it still suffered from a short life cycle, suggesting further studies on the stability of Si-NPs/graphene nanocomposite. Saulnier et al also studied the use of multilayer CVD grown graphene on nickel substrate as the anode material [ 271 ]. The effect of films’ morphological defects on the sustainability of discharge capacity at high speed was highlighted.…”
Section: Applications Of Cvd Graphenementioning
confidence: 99%
“…The nanocomposite was tested as an anode in button lithium-ion battery giving a high energy capacity, yet it still suffered from a short life cycle, suggesting further studies on the stability of Si-NPs/graphene nanocomposite. Saulnier et al also studied the use of multilayer CVD grown graphene on nickel substrate as the anode material [ 271 ]. The effect of films’ morphological defects on the sustainability of discharge capacity at high speed was highlighted.…”
Section: Applications Of Cvd Graphenementioning
confidence: 99%
“…Multiple attempts have shown that graphene thin films can be deposited via CVD [341][342][343], sputtering [344] and PLD [345]. Reddy et al [342] prepared N-doped graphene thin films for the anode via CVD.…”
Section: Anodesmentioning
confidence: 99%
“…According to the authors, the films exhibited a reversible discharge capacity of 0.05 mAh/cm 2 under the current density of 5 μA/cm 2 after 50 cycles. Saulnier et al [341]…”
Section: Anodesmentioning
confidence: 99%
See 1 more Smart Citation